Analysis and design of sea-water Yagi Monopole antennas - Hao, Yu Xiao (2018)
This report presents a study of Sea-water Yagi monopole antenna made of sea-water. Antenna as an essential device for radio system that is in high demand in a wide range of wireless devices. Most of antenna are conventional antenna that is made of metal material, beyond that, liquid antennas have attracted increasing attention in recent years, this report mainly analyzed sea-water monopole antenna, which comprises a driven element with a probe-fed and a cylinder container hold by a translucent PLA tube to work as parasitic element. One water-based liquid, namely salty water is carefully studied from and antenna design point of view, the experimental data are obtained over a temperature range 0 ~ 28 deg. Commercial software Ansoft HFSS is used to simulate and verify the theoretical study. The parasitic element can be convert into director or reflector by changing the height of sea-water filled in parasitic element cylinder. This report has demonstrated the unique features of sea-water monopole antenna. The knowledge gained in this experiment and simulation analysis is very valuable for future sea-water based antenna development.